Effect of Training Work-family Conflict Management on Increasing the Quality of Work Life among the Female Employees of Hospital - salman zarei; ahmad kazemipour (Muhandisī-i bihdāsht-i ḥirfah/ī, 2020)
Background and Objective: Nowadays, work-family issues have gained special importance for employees, families, and organizations. Work-family conflict is a kind of interrole conflict referring to the incompatibility between the pressures and demands in work and family domains leading to stress and numerous problems. Therefore, the aim of this study was to examine the impact of training work-family conflict management on the quality of work life (QWL). Materials and Methods: This quasi-experimental study as a pretest-posttest design with a control group was performed on the study population consisting of women working in the hospital of Nurabad city, Iran. A total of 30 female employees were selected through the voluntary sampling method and were randomly divided into the two groups of experiment and control. Subjects of the intervention group received six sessions of training regarding work-family conflict management. The data were collected using the Quality of Work Life Questionnaire (QWLQ) and were analyzed by the analysis of covariance (ANCOVA). Results: The results of ANCOVA showed that training management skills concerning a work-family conflict can enhance the QWL of employees. Following the adjustment for the pre-test scores, a significant difference was observed between the post-treatment scores of the intervention and control groups (P<0.01). Conclusion: According to the finding of this study, the application of management skills for work-family conflict might assist the female staff of the hospital to better cope with the inevitable problems and stresses caused by work-family conflict. As a result, the QWL of these individuals will get improved.